The Proposals of Administrative Judiciary Reforms in Poland - Chmielarz-Grochal, Anna (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The aim of the article is to present the basic assumptions of the reforms of the Polish administrative judiciary. The planned and implemented reforms concerned both the model of administrative judiciary system, as well as the model of adjudication and rules of procedure before administrative courts. The analysis of the implemented solutions, starting from the period of the Second Polish Republic, made it possible to formulate a thesis that the administrative judiciary was subject to evolutionary (developmental) reforms. The article mainly concerns systemic issues, as the creation of a separate, independent, two-instance administrative judiciary was a priority postulate for reforms initiated after Poland regained independence, which appeared in later reform proposals. As the analysis shows, this postulate was fully implemented after the entry into force of the Constitution of the Republic of Poland of 1997.